Abscopal Effect Following Proton Beam Radiotherapy in a Patient With Inoperable Metastatic Retroperitoneal Sarcoma - Brenneman, Randall J.; Sharifai, Nima; Fischer-Valuck, Benjamin; Hassanzadeh, Comron; Guzelian, Jeffrey; Chrisinger, John S. A.; Michalski, Jeff M.; Oppelt, Peter; Baumann, Brian C. (Frontiers in Oncology, 2019)
Background: Retroperitoneal sarcomas (RPS) are rare and primarily managed with surgery, which improves local recurrence-free and overall survival. Radiation can improve local control or provide palliation for inoperable or metastatic RPS by eliciting tumor cell death via irreparable DNA damage. In extraordinary circumstances radiation-induced cell death promotes immune-mediated regression of non-irradiated lesions in a process termed the abscopal effect. Abscopal effects are rare and incompletely understood, involving a balance of radiation’s immunogenic and immunosuppressive effects. There are currently no methods to predict abscopal responses following radiotherapy. Case reports documenting post-radiotherapy abscopal effects provide additional information to better characterize these responses and to inform ongoing and future clinical trials attempting to harness radiation-induced immune responses to improve outcomes with systemic therapy, such as SARC-032, a cooperative group trial of pre-operative radiation +/- pembrolizumab. We present a case of inoperable metastatic RPS treated with proton radiotherapy with complete responses of un-irradiated metastases. Case Presentation: A 67 year-old female with inoperable metastatic unclassified round cell RPS was treated with palliative proton radiotherapy only to the primary tumor. Following completion of radiotherapy, the patient demonstrated complete regression of all un-irradiated metastases, and near complete response of the primary lesion without additional therapy. Conclusions: Metastatic RPS is typically managed with first-line chemotherapy, with objective response rates <50%. We present a case of inoperable metastatic RPS treated with palliative proton radiotherapy for rapidly progressive disease who had complete regression of non-irradiated metastases consistent with the abscopal effect. To our knowledge this is the first case report describing abscopal effects in inoperable metastatic RPS treated with proton radiation and is among the first case reports of an abscopal effect in a patient treated with proton therapy regardless of disease site. Further investigation is warranted regarding the benefit of proton radiation to primary tumors for inoperable metastatic RPS.